Social entrepreneurship in medical education: Model to establish SinnoLABs (social innovation labs) for health sciences universities - Juhi M. Raut; Abhishek U. Joshi (Journal of Family Medicine and Primary Care)
Social entrepreneurship is a cross-cutting competency. It draws on knowledge from various disciplines and personal experiences. Health, social sciences and humanities are usually technically sound but lack specific business knowledge and skills. Entrepreneurial education makes it possible to establish training environments where students join as ‘novices’, develop skills and undergo experiences that help them build capable profiles and prepare for their professional careers in today's economy. It is important to note that the development of skills for social entrepreneurship is increasingly demanded in all disciplinary fields. Interest from the academic, business and civil society in social innovation and social entrepreneurship is growing rapidly since social value creation and social innovation are considered vital to the social entrepreneurship phenomenon. The innovation process aims to fill the gap between working life and educational framework so that students can develop innovation capabilities they will need during their careers. Taking cognizance of the importance of social innovation and entrepreneurship, the Government of India formulated a policy for Biomedical Innovation and Entrepreneurship in 2022. Our University established a first of its kind Social Innovation Lab (SinnoLAB) under a Collaborative European Union Project. Our University is one of the collaborating partners and the only health sciences university to set up a SinnoLAB in India. We discuss in this article how a SinnoLaB can be set up, its functions, need for such labs in medical institutes, its role in medical education and its beneficiaries and propose that other health sciences institutes can also take up social innovation and entrepreneurship considering the benefits to all stakeholders.